JA:2021-36. NY Nudging Dairy Safety Project: Re-engineering Best Management Safety Practices on NY Dairies. Issue 3 (2nd July 2020) - Sorensen, Julie; Carrabba, James; Birk-Domino, Helle; McNamara, John; Van den Broucke, Stephan; Meyerhoff, Anna; Todd, Ryan
ABSTRACT: Purpose : Nudging incorporates adjustments to a task or environment in ways that nudge people to do the right thing, sometimes without them even having to think about it. The project will seek to address dairy labor and safety challenges by examining the efficacy of "nudging" principles to improve worker safety and the efficiency of work processes. Methods : Researchers will ask farmers to select three issues on the farm that they would like to resolve. Data will be collected to further define and elucidate these issues (i.e. survey data, mapping the task environment, videotaping tasks, and interviewing workers). Each of these issues will be assessed by the project team to select one issue that fulfills the following criteria: 1) the root cause is a behavioral problem; 2) safety could be incorporated into the solution; and 3) it could be reasonably implemented and evaluated. Project team members will then conduct a behavioral reduction, map the behavior, assess the behavioral components, apply a priority filter, and develop a solution using the cognitive strategy best suited to the issue. Results/Findings : Interviews and surveys will be conducted before and after the implementation of nudging projects to evaluate: 1) the process and 2) the outcomes (are safer practices being adopted by workers? If yes, has time to perform the task been reduced? Has effort to perform the task been reduced? Have other efficiencies been created?). Practical Application : Videos and one-page summaries of nudging projects will be created. These will be featured on the Northeast Center for Occupational Health and Safety (NEC) website and circulated at events such as the NY Farm Show and Empire Farm Days. NEC trainers will share one-pagers with farmers at safety trainings and during worksite safety walk-throughs.